2024
DOI: 10.1002/anie.202402634
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Photochemical Cascade Process Boosting Smart Ultralong Room‐Temperature Phosphorescence in Bismuth Halides

Chang Xing,
Zhenhong Qi,
Bo Zhou
et al.

Abstract: Molecular ultralong room‐temperature phosphorescence (RTP), exhibiting multiple stimuli‐responsive characteristics, has garnered considerable attention due to its potential applications in light‐emitting devices, sensors, and information safety. This work proposes the utilization of photochemical cascade processes (PCCPs) in molecular crystals to design a stepwise smart RTP switch. By harnessing the sequential dynamics of photo‐burst movement (induced by [2+2] photocycloaddition) and photochromism (induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 53 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Studies have shown that the luminescence in such materials primarily arises from electron transfer processes between the organic and inorganic components. The zero-dimensional anionic copper halide inorganic cluster motifs have been demonstrated as the important functional units for high-performance all-in-one (AIO) types of luminescent compounds. In addition, the covalent bonds between the two components provide pathways for efficient electron transfer, which is typically considered a crucial prerequisite for high luminescence efficiency of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the luminescence in such materials primarily arises from electron transfer processes between the organic and inorganic components. The zero-dimensional anionic copper halide inorganic cluster motifs have been demonstrated as the important functional units for high-performance all-in-one (AIO) types of luminescent compounds. In addition, the covalent bonds between the two components provide pathways for efficient electron transfer, which is typically considered a crucial prerequisite for high luminescence efficiency of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of ionic compound, metal halide hybrids (MHHs) mainly consist of organic cations and metal halide polyhedra anions. Due to their wide composition and structure tunability, easy preparation, and excellent optical properties, MHHs have been attracted enormous attention in optoelectronic fields including X-ray scintillator, solid-state lighting, anticounterfeiting, information encryption, and stimulus response. , Recently, [2 + 2] photocycloaddition was successfully employed to control the room-temperature phosphorescence switch and photochromism in zero-dimensional (0D) bibased MHHs . Endowing MHHs with reversible photochromism could significantly broaden their applications in fields such as high-level-security information encryption and optical data storage.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Recently, [2 + 2] photocycloaddition was successfully employed to control the room-temperature phosphorescence switch and photochromism in zero-dimensional (0D) bibased MHHs. 51 Endowing MHHs with reversible photochromism could significantly broaden their applications in fields such as high-level-security information encryption and optical data storage. Different from CPs and MOFs with rational structural tunability, the ionic nature of MHHs determines the poor predictability and tunability of their structures due to random assembly between organic cations and anions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various applications of organic crystal luminescent materials have made significant progress, such as laser sensors, photoelectron conversion, and optical signal transduction . As the key to expanding the application scope, achieving the modulation of the solid-state optical properties of the target organic molecule is challenging. At the same time, the solid-state aggregation fluorescence quenching effect of organic molecules must also be considered to avoid strong emissivity in the dispersed state and weak or no emissivity in the aggregated state.…”
Section: Introductionmentioning
confidence: 99%